The Greenland Ice Sheet as a hot spot of phosphorus weathering and export in the Arctic. Issue 2 (6th February 2016) - Hawkings, Jon; Wadham, Jemma; Tranter, Martyn; Telling, Jon; Bagshaw, Elizabeth; Beaton, Alexander; Simmons, Sarah‐Louise; Chandler, David; Tedstone, Andrew; Nienow, Peter
Abstract: The contribution of ice sheets to the global biogeochemical cycle of phosphorus is largely unknown, due to the lack of field data. Here we present the first comprehensive study of phosphorus export from two Greenland Ice Sheet glaciers. Our results indicate that the ice sheet is a hot spot of phosphorus export in the Arctic. Soluble reactive phosphorus (SRP) concentrations, up to 0.35 µ M, are similar to those observed in Arctic rivers. Yields of SRP are among the highest in the literature, with denudation rates of 17–27 kg P km −2  yr −1 . Particulate phases, as with nonglaciated catchments, dominate phosphorus export (>97% of total phosphorus flux). The labile particulate fraction differs between the two glaciers studied, with significantly higher yields found at the larger glacier (57.3 versus 8.3 kg P km −2  yr −1 ). Total phosphorus yields are an order of magnitude higher than riverine values reported in the literature. We estimate that the ice sheet contributes ~15% of total bioavailable phosphorus input to the Arctic oceans (~11 Gg yr −1 ) and dominates total phosphorus input (408 Gg yr −1 ), which is more than 3 times that estimated from Arctic rivers (126 Gg yr −1 ). We predict that these fluxes will rise with increasing ice sheet freshwater discharge in the future. Key Points: Phosphorus concentrations in meltwaters are significant and higher than previously appreciated Ice sheet phosphorus yields are at least 10 times higher than riverine catchments The ice sheet plays a more important role in the Arctic phosphorus cycle than previously thought